2016
DOI: 10.1038/npp.2016.229
|View full text |Cite
|
Sign up to set email alerts
|

The Immunology of Behavior—Exploring the Role of the Immune System in Brain Health and Illness

Abstract: Given the well-known impact of stress on psychiatric disease, there is a rich basic science literature using a variety of Neuropsychopharmacology REVIEWS (2017) 42, 1-4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 20 publications
(18 reference statements)
0
35
0
Order By: Relevance
“…Differing from both the domain-focused training, as well as compensatory cognitive remediation approaches, TCT emphasizes training of early phases of perceptual processing while simultaneously requiring close engagement of attentional control and prefrontal predictive and response selection operations. This intervention has been demonstrated to evoke neuroplasticity in sensory ( Dale et al, 2015 , Popov et al, 2011 ), subcortical ( Ramsay et al, 2017 ), and higher-order ( Subramaniam et al, 2014 ) cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Differing from both the domain-focused training, as well as compensatory cognitive remediation approaches, TCT emphasizes training of early phases of perceptual processing while simultaneously requiring close engagement of attentional control and prefrontal predictive and response selection operations. This intervention has been demonstrated to evoke neuroplasticity in sensory ( Dale et al, 2015 , Popov et al, 2011 ), subcortical ( Ramsay et al, 2017 ), and higher-order ( Subramaniam et al, 2014 ) cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions targeting tonic craving may in turn dampen phasic response to alcohol administration or cues, thus assessing craving in multidimensional fashion and accounting for combined phasic and tonic effects appears warranted. To that end, a recent human laboratory study found that a novel neuroimmune medication (ibudilast) reduced tonic craving compared to placebo (captured by the PACS) yet there were no medication effects on alcohol- or cue-induced phasic craving ( Ray et al, 2017 ). This serves to illustrate the complex clinical interplay between tonic and phasic craving and its treatment implications.…”
Section: Discussionmentioning
confidence: 99%
“…More specific, increased endurance (higher scores on the reduced Cooper test) seemed related to reduced number of pain sites (Table 5 ). At first, this might resemble activity-induced pain modulation or hypoalgesia (Naugle et al, 2013 ; Jones et al, 2014 ; Saanijoki et al, 2017 ). However, the study design does not allow such an evaluation.…”
Section: Discussionmentioning
confidence: 99%